2016
DOI: 10.1080/02705060.2016.1259127
|View full text |Cite
|
Sign up to set email alerts
|

Estimating in situ isotopic turnover in Rainbow Trout (Oncorhynchus mykiss) muscle and liver tissue

Abstract: Stable isotope analysis (SIA) is a powerful tool for assessing food webs and diet. However, the underlying assumptions that stable isotope ratios in an organism's tissues reflect that of its present diet may be complicated by isotopic turnover and retention time. Quantification of in situ isotopic turnover of study organisms and different tissues via field studies is essential to inform scientifically sound food web and diet studies utilizing SIA. Rainbow Trout white muscle and liver tissue were collected mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Based on an ectotherm tissue-specific model with body mass as a variable, the isotopic half-life of liver tissue samples from a fish of average weight in our study is 52 days (Vander Zanden et al, 2015). Further, an in situ study of rainbow trout (Oncorhynchus mykiss) found that it takes ∼5-6 months for the liver tissue of a consumer to be at equilibrium with the stable isotope signature of a new diet (Skinner et al, 2017). Stable isotope turnover time may be slower in the winter than in the fall, spring, and summer because cooler water can decrease the turnover time in fish (Maitland et al, 2021).…”
Section: Stable Isotope Issues and Considerationsmentioning
confidence: 76%
“…Based on an ectotherm tissue-specific model with body mass as a variable, the isotopic half-life of liver tissue samples from a fish of average weight in our study is 52 days (Vander Zanden et al, 2015). Further, an in situ study of rainbow trout (Oncorhynchus mykiss) found that it takes ∼5-6 months for the liver tissue of a consumer to be at equilibrium with the stable isotope signature of a new diet (Skinner et al, 2017). Stable isotope turnover time may be slower in the winter than in the fall, spring, and summer because cooler water can decrease the turnover time in fish (Maitland et al, 2021).…”
Section: Stable Isotope Issues and Considerationsmentioning
confidence: 76%
“…To test the relationship between short-term and longer-term diets, we compared our cross-sectional data from stomach contents to individual stable C and N isotope ratios which provide an integrative measure of diet over weeks to months (Peterson and Fry 1987 ; Bolnick et al 2002 ), with in situ measures of muscle tissue isotopic turnover exceeding 5 months in coldwater rainbow trout (Skinner et al 2017 ). We tested for a relationship between diet and muscle tissue stable isotope ratios using permutational analysis of variance (PERMANOVA) with diet composition as the multivariate response, and δ 13 C and δ 15 N values as explanatory variables using the ‘vegan’ package v2.5–6 in R (Oksanen et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Differences in δ 13 Cˈ between muscle and liver suggest that most individuals fed on prey with similar δ 13 C (+/-2.5‰) over weeks and months, while a few individuals switched to prey sources or locations with different δ 13 C. Previous research demonstrates differences in isotope turnover rates between liver and muscle tissue in fish [108][109][110] due to the association with metabolism rather than growth in liver tissue [108]. Hesslein et al estimated the half-life of δ 13 C and δ 15 N to be 101 days in juvenile Broad Whitefish muscle tissue, but due to slow growth in adult fish, it is likely that the turnover rate for muscle tissue could be years [27].…”
Section: Differences In δ 13 Cˈand δ 15 N Between Tissuesmentioning
confidence: 99%